Under pressure : understanding and managing the pressure and stress of work - Sartain, Denis (Marshall Cavendish, 2010)
Everyone needs a certain level of pressure in order to achieve things at work. But when we go beyond pressure, we start to experience stress which is negative, counter-productive and potentially disastrous. Yet stress, especially at work, is a subject that is often ignored because to recognise it can be interpreted as a sign of weakness.